WRITING ON THE WALL - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
'We have the right to information!' was the battle-cry when fifty delegates of farmers' organisations from the South, mainly Africa, set up a network at a meeting in Lorraine, France in early April 1998, convened by the organisation French Farmers...